Evaluation of Yield and Yield Components of Two Potato Cultivars in Khorasan Razavi Province of Iran - Setareh Foroghian; Mohammad Reza Asgharipour; Mehdi Ghiafeh Davoodi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
In order to study the yield and yield components of two potato cultivars, an experiment was conducted as a split plot based on a randomized complete block design with three replicates. The experiment was performed in two locations, Jolgeh-Rokh district, and Fariman city, in professional farmers’ fields in Khoarasan Razavi province. The main plots consisted of two potato cultivars, Agria and Fontane cultivars (medium maturing), which were identified as the main cultivars used in chips production factories in the Province. Our results showed higher potential of Agria cultivar for production of stems per plant compared to Fontana cultivar. Both stem number and tuber number per plant along with tuber weight and tuber yield were higher in Fariman location than in Jolgeh-Rokh.